Transfer Pengetahuan antar Generasi pada Perusahaan Keluarga - , Gabriella Hanny Kusuma; , DR. Nurul Indarti, Sivilekonom, Cand. Merc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to assess the inter-generational transfer of knowledge that occurs in the family company in Indonesia . This study is a qualitative research case-study. Theoritical sampling methods used in this study. Samples from this study amounted to 14 companies consisting of 23 people as research participant. Data collection using in-depth and semi-structured interview, recorded and transcribed, and then analyzed by the method of content analysis ( content analysis). Processing Data also use a visual map and temporal bracketing. Validity and reliability for this study used triangulation of data sources. Participants also involved in checking the results of the interview transcribed (member checking). Results showed that the process of knowledge transfer between generations in a family company in Indonesia took place slowly and gradually. Most of the knowledge being transferred is tacit knowledge and thus require direct interaction of the predecessor and successor . Physical presence of the predecessor and successor and the successor to the routine corporate involvement is an important element in the transfer of knowledge. Knowledge which transferred by the predecessor to the successor is related to products knowledge, business management knowledge, technical knowledge, and philosophical knowledge. Transfer of knowledge there are planned and unplanned. Planned or unplanned knowledge transfer highly dependent on predecessor. There are two stages in the knowledge transfer process, namely initiation and implementation. The predecessor and successor are the main actors in the knowledge transfer process between generations. Role of successor increased steadily with decreasing of predecessor role in the company. Successor roles as an assistant, manager, and then Leader of company. Keywords: Qualitative